Prostaglandins and related compounds from the polychaete worm Americonuphis reesei Fauchald (Onuphidae) as possible inducers of gonad maturation in Penaeid shrimps - D’ Croz, Luis; Wong V., Luis; Grupta, Mahabir (Revista de Biología Tropical, 1988)
<span id="docs-internal-guid-86f794e7-111b-caad-da8e-e098d703ec90" style="font-size: 13.333333333333332px; font-family: Arial; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline;">During the past few years, mariculturists in Panama have been using the Onuphid polychaete tube-worm Americonuphis reesei Fauchald (Fauchaid 1973) as a dietary supplement in order to accelerate gonad maturation in the penaeid shrimps Penaeus vannamei Boone and P. stylirostris Stimpson. The success of this supplement has led to a small fishery of the worm and its export to shrimp farmers in Ecuador, Belize and Guatemala. The worm is frozen and fed chopped to the adult shrimps. Mariculturist’s efforts to use pelletized worms failed to produce the expected results. This suggested us that the bioactive compounds are labile. Visual observation of a large lipid content in the worm tissues suggested that the active compounds might be lipidic in nature. The prostaglandins (PGs), lipid compounds derived from arachidonic acid (AA), are active molecules with high hormone like activity (Tortora and Anagnostakos 1981). These molecules are known to play an important role in the reproductive cycle of numerous species. For example, PGs induce gonad maturation and gamete release in marine bivalves and gastropods (Morse et al 1977).